2020
DOI: 10.1177/1049909120907599
|View full text |Cite
|
Sign up to set email alerts
|

“Online Training Is Great but Human Interaction Is Better”: Training Preferences of VA Interdisciplinary Palliative Care Consult Teams

Abstract: A growing body of research has examined modalities for delivering palliative care education; however, we know little about education and training preferences of VA interdisciplinary Palliative Care Consult Teams (PCCT). In the BEACON II study, we explored training preferences of PCCTs from 46 Veterans Affairs Medical Centers (VAMCs) participating in either a multisite webinar or a small group, in-person workshop. We interviewed participants by telephone seven to eight month post-training. In all, 75.9% preferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
5
1
Order By: Relevance
“…Because changes in practice patterns can be challenging and slow, especially in large organizations, future implementation trials might consider other approaches to behavior change or outcomes at other points in the pathway from training to patient outcomes. In conclusion, although an in-person workshop was the training modality preferred by providers from both groups in our analyses of qualitative interviews, 53 the teleconference is perhaps more economical and resource efficient. These findings can inform considerations of the optimal approaches to palliative care education and training and optimize further nationwide dissemination of best practices for end-of-life care in both VA and non-VA settings.…”
Section: Discussionmentioning
confidence: 74%
“…Because changes in practice patterns can be challenging and slow, especially in large organizations, future implementation trials might consider other approaches to behavior change or outcomes at other points in the pathway from training to patient outcomes. In conclusion, although an in-person workshop was the training modality preferred by providers from both groups in our analyses of qualitative interviews, 53 the teleconference is perhaps more economical and resource efficient. These findings can inform considerations of the optimal approaches to palliative care education and training and optimize further nationwide dissemination of best practices for end-of-life care in both VA and non-VA settings.…”
Section: Discussionmentioning
confidence: 74%
“…Learners benefited from the flexible learning environment and demonstrated that they were able to complete the course (both the required and optional content). A qualitative interview study by Williams et al ( 19 ) revealed that (1) being actively engaged, (2) having the opportunity to interact and network, (3) finding meaning and relevance, and (4) exercising reciprocity are common training preferences for learning PC. For this reason, PCA:Hep, similar to other online trainings in communication and PC, ( 26 , 27 , 28 ) integrated roleplay scenarios in addition to didactic lectures and patient‐provider demonstrations.…”
Section: Discussionmentioning
confidence: 99%
“…We sought to improve self‐efficacy of PC skills by balancing web‐based learning with the interactive practice sessions, as this approach has been shown to be acceptable ( 18 ) and aligns with preferred training practices of health care providers learning PC. ( 18 , 19 ) Additionally, we explored whether the trained hepatologists would translate these skills outside the PAL‐LIVER trial, thereby providing an extra layer of support to all patients. The purpose of this paper is to describe the formative and summative evaluations of PCA:Hep.…”
mentioning
confidence: 99%
“…Have published an article from their NSCPM course project in a peer-reviewed journal placed in different Nordic locations once the Covid-19 pandemic allows it. 17 The networking aspects, the international faculty, and the reputation for high quality have made the course stay attractive, also when Sweden 18 and Finland 19 in later years have organized national courses to obtain formal approval in PM.…”
Section: Discussionmentioning
confidence: 99%